ANALISIS PENERIMAAN TEKNOLOGI FINANCIAL AGGREGATOR CEKAJA.COM TERHADAP BEHAVIOR INTENTION MELALUI PENDEKATAN TEORI PERILAKU RENCANAAN (THEORY OF PLANNED BEHAVIOR ATAU TPB) (Studi Pada Masyarakat Kota Pangkalpinang) - Laurensia Widyastuti; Suhaidar Suhaidar (Jurusan Akuntansi, Universitas Bangka Belitung, 2020)
The purpose of this research study is to analyze and empirically prove the effects of attitude towards behavior, subjective norms, and perceived behavioral control on behavioral intention related to accepting the financial aggregator technology of CekAja.com. It is a quantitative study of Pangkalpinang society using an incidental sampling technique. To determine the sample size, the Maximum Likelihood Estimation (MLE) method was used. To collect the primary data used in this study, this writer conducted field research (by means of online and in person questionnaires) as well as a review of relevant literature. To analyze the data, this writer used the Covariance Based Structural Equation Modeling (CB-SEM) approach using the Analysis of Moment Structure (AMOS) Version 22 and Statictical Product and Service Solution (SPSS) Version 25 analysis tools. The results of the research showed that attitude towards behavior positively and significantly influenced the behavioral intention of Pangkalpinang society in accepting the financial aggregator technology of CekAja.com; subjective norms did not have significant and positive influence on the behavioral intention of Pangkalpinang society in accepting the financial aggregator technology of CekAja.com; while perceived behavioral control positively and significantly influenced the behavioral intention of Pangkalpinang society in the accepting the financial aggregator technology of CekAja.com.